Information system adoption and usage: validating UTAUT model for Bangladeshi SMES - Mursalin, Md. Jabir Al (BRAC University, 2013)
Small and medium enterprises (SME) are an integral part of any country’s economy. Therefore, their existence, operational efficiency and effectiveness must be ensured. Implementation of information system (IS) in business value chain allows organizations to enhance this efficiency thus enables organizations to grow and sustain. This research explores 255 Bangladeshi SMEs to conceptualize current trend of IS usage and validates four constructs of unified theory of acceptance and use of technology (UTAUT) model to explain IS adoption behavior. The outcome of the study shows that, though a number of Bangladeshi SME’s are exposed to computer based IS, their usage, in most cases, are limited to operational level of activities. SMEs are also less concerned about the further development of IS and allocated a minimum budget for IS development. It is also found that the adoption and usage of IS by the Bangladeshi SMEs are strongly influenced by performance efficiency, effort efficiency and facilitating condition and moderately influenced by social influence.